2002
DOI: 10.1093/pcp/pcf148
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin Isoforms Responsive to Salt and Water Stresses and Phytohormones in Radish Seedlings

Abstract: ;Aquaporins in the plasma and vacuolar membranes play a key role in the intercellular and intracellular water transport in plants. First, we quantitated the absolute amounts for mRNAs of eight aquaporin isoforms in hypocotyls of radish seedlings. Then, we investigated the effects of salt and water stresses (150 mM NaCl, 300 mM mannitol and 20% polyethylene glycol) and phytohormones (gibberellic acid, abscisic acid and brassinolide) on the mRNA and protein levels of aquaporins in the plasma membrane (RsPIP1-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 35 publications
(47 reference statements)
8
96
0
5
Order By: Relevance
“…OsPIP1;2, OsPIP1;3, OsPIP2;1, OsPIP2;3, OsPIP2;4, OsPIP2;5 and OsPIP2;6, were transcribed at higher rates in roots than leaves and only one PIP gene, OsPIP2;7, followed the pattern of mRNA accumulation of higher levels in leaves than roots. Inconsistency between aquaporin expression at the mRNA level and protein accumulation was also noted in a previous study [8,30]. These authors postulated that post-transcriptional mechanisms resulted in this, e.g.…”
Section: Pip Expression In Upland Rice and Lowland Rice Under Normal supporting
confidence: 63%
See 1 more Smart Citation
“…OsPIP1;2, OsPIP1;3, OsPIP2;1, OsPIP2;3, OsPIP2;4, OsPIP2;5 and OsPIP2;6, were transcribed at higher rates in roots than leaves and only one PIP gene, OsPIP2;7, followed the pattern of mRNA accumulation of higher levels in leaves than roots. Inconsistency between aquaporin expression at the mRNA level and protein accumulation was also noted in a previous study [8,30]. These authors postulated that post-transcriptional mechanisms resulted in this, e.g.…”
Section: Pip Expression In Upland Rice and Lowland Rice Under Normal supporting
confidence: 63%
“…Different PIP genes exhibit different expression patterns. Water deficit was shown to enhance the expression of rice OsPIP1a and OsPIP2a [5], tomato TRAMP [6], Nicotiana excelsior NeMip2 and NeMip3 [7] and radish RsPIP2 [8], but reduced Nicotiana glauca NgMIP4 [9] and rice RWC1 [10]. In a recent study, both up-and down-regulation of PIP expression were observed under water deficit induced by mannitol in Arabidopsis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellic acid and abscisic acid suppressed the levels of mRNAs of RsPIP2-1, RsPIP2-2 and RsPIP2-3 and the protein level of RsPIP2-1 in roots. On the other hand, the protein levels of RsPIP1-group members and RsTIPs were scarcely changed by these phytohormones [104].…”
Section: Relationships Between Plant Aquaporins and Hormonesmentioning
confidence: 94%
“…Brassinolide may control aquaporin activities in Arabidopsis thaliana, which has been shown to be involved in the modification of the water-transport properties of cell membranes [105], however, mRNA and protein levels of aquaporin isoforms in root and shoot of radish were not affected by brassinolide treatment [104]. Ethylene significantly increased stomatal conductance, root hydraulic conductivity (L p ), and root oxygen uptake in hypoxic seedlings.…”
Section: Relationships Between Plant Aquaporins and Hormonesmentioning
confidence: 98%
“…Nutritional deficiency in general decreases the expression of Lp and aquaporin genes in roots [4], however, specific genes were induced under special conditions, such as Arabidopsis NIP5;1 by boron-deficiency [24] and Arabidopsis TIP2;1 by nitrogen-deficiency [17]. Low temperature [13], phytohormones [23], and far-red light [22] also regulated the expression of plant aquaporins. These observations indicate that adequate regulation of water homeostasis via aquaporins is common in plant cells adjusting to various environments.…”
Section: Water Transport Of Barley Pipsmentioning
confidence: 99%